Competition at the soybean V6 stage affects root morphology and biochemical composition. (17th December 2019) - Rockenbach, A. P.; Rizzardi, M. A.
Abstract: The experiment was conducted in the 2016/17 crop season in a greenhouse at Passo Fundo University, Brazil. We hypothesised that the morphological characteristics and biochemical and anatomical composition of soybean roots and shoots, when competing with weeds during different growth periods, are negatively affected, so current concepts of competition between plants should also consider changes in plant roots. The soybean cultivar P 95R51 and horseweed ( Conyza bonariensis ) were used. The treatments consisted of the presence or absence of weeds during different coexistence periods of soybean with horseweed. The periods were V0–V3, V0–V6, V0–R2, V3–R6, V6–R6 and R2–R6, where V0 was the date of soybean sowing and V3, V6, R2 and R6 were phenological stages of the crop. Two fresh roots were used to examine morphological traits. Four roots were used for quantification of dry matter and secondary metabolites. Root length was reduced by 21%, 14% and 20% when competing with a weed in the V0–V3, V0–V6 and R2–R6 coexistence periods, respectively. Total phenol content in the V0–V6 and V0–R2 periods was reduced when plants were in competition with weeds; a similar trend was found for flavonoids in the V0–V6 period. Soybean–horseweed competition from crop emergence to the V6 stage, in general, affects shoot and root morphological traits and the biochemical composition of the soybean roots. The presence of horseweed at the V3, V6 and R2 stages does not negatively alter the traits evaluated. Root anatomical composition is not modified during all coexistence periods with horseweed. Abstract : Soybean‐horseweed competition from the crop emergence to the V6 stage, in general, affects the shoot and root morphological traits and the biochemical constitution of soybean roots.